Dinamika Perkembangan Modal Ventura di Indonesia: Sebuah Tinjauan Literatur - Arsyaf Tampubolon; Gabril Dhava Obrien Sinamo (MTU PRESS, 2026)
Venture capital has become a strategic financing instrument for the growth of startups and MSMEs in Indonesia, particularly in driving the digital economic transformation. However, its development faces various complex challenges, including the gap between regulation and practice as well as the phenomenon of philosophical shifts that threaten its fundamental characteristics. This research aims to systematically analyze the dynamics of venture capital development in Indonesia through a comprehensive literature review approach. The method used is descriptive qualitative with library research, analyzing selected scholarly articles that discuss regulations, investment practices, comparison of conventional and sharia models, as well as industrial development challenges. The findings reveal three main results. First, there is a paradoxical development pattern where the number of Venture Capital Companies tends to decrease while total assets increase significantly, indicating industrial consolidation. Second, a significant gap exists between regulatory ideals and practices, reflected by the dominance of debt financing compared to equity participation, as well as the